Genome-Wide Dissection of Sorghum B3 Transcription Factor Family Identifies SbLAV1 as a Critical Transcriptional Regulator of Starch Biosynthesis in Developing Sorghum Grains - Xiangling Gong; Jing Li; Zheyu Yan; Anqi Sun; Yi Zheng; Min Yin; Qianlin Xiao; Zhizhai Liu (Plants)
Sorghum (Sorghum bicolor L.) is the fifth largest cereal crop in the world and widely used in the fields of food, feed, brewing, and fuel, while knowledge is mostly limited for sorghum grain development, including starch biosynthesis. B3 family transcription factors (TFs) play a crucial role in plant development, including grain development, dormancy, and storage of nutrients. In the present study, a comprehensive analysis of sorghum B3 genes was performed, and a total of 76 related genes were identified to be distributed on 10 chromosomes across the whole sorghum genome. According to the sequence features, the sorghum B3 family members were divided into four sub-families of ARF, RAV, LAV, and REM. Multiple elements, i.e., light-responsive elements, phytohormone-responsive elements, growth and development-related elements, and stress-responsive elements, were discovered to be located within the 2000 bp upstream of the translation start site. Results of expression analysis across multiple tissues suggested significantly different expression patterns of sorghum B3 genes. Further assays confirmed that SbLAV1, which belonged to the LAV subfamily of B3, co-expressed with 15 key starch biosynthesis-related genes (SBRGs), and the corresponding product of SbLAV1 could activate the promoter activities of multiple key SBRGs. Collectively, the integrative results of the present study indicate that B3 family members, including SbLAV1, might play critical roles in starch biosynthesis and grain development in sorghum.